Type 1 vomeronasal receptors expressed in the olfactory organs of two African lungfish, Protopterus annectens and Protopterus amphibius. Issue 1 (26th September 2022) - Nakamuta, Shoko; Yamamoto, Yoshio; Miyazaki, Masao; Sakuma, Atsuhiro; Nikaido, Masato; Nakamuta, Nobuaki
Abstract: Lungfish are the fish related most closely to tetrapods. The olfactory organ of lungfish contains two distinct sensory epithelia: the lamellar olfactory epithelium (OE) and the recess epithelium (RecE). Based on their ultrastructural and histological characteristics, the lamellar OE and the RecE are considered to correspond respectively to the teleost OE and a primitive vomeronasal organ (VNO). In tetrapods, the OE and VNO have been shown to express different families of olfactory receptors; for example, in mammals, the OE expresses odorant receptors and trace amine‐associated receptors, while the VNO expresses type 1 (V1Rs) and type 2 (V2Rs) vomeronasal receptors. In the present study, we examined the expression of V1Rs in the olfactory organs of two African lungfish, Protopterus annectens and Protopterus amphibius . RNA sequencing and phylogenetic analyses identified 29 V1R genes in P. annectens and 50 V1R genes in P. amphibius . Most V1Rs identified in these lungfish were classified as the tetrapod‐type V1Rs initially found in tetrapods and distinct from fish‐type V1Rs. In teleost, which all lack a VNO, all olfactory receptors are expressed in the OE, while in Xenopus V1Rs are expressed exclusively in the OE, and not in the VNO. In situ hybridization analysis indicated that lungfish V1Rs were expressed mainly in the lamellar OE and rarely in the RecE. These results imply that V1R expression in lungfish represents an intermediate step toward the complete segregation of V1R expression between the OE and VNO, reflecting the phylogenetic position of lungfish between teleosts and amphibians. Abstract : Lungfish has two distinct sensory epithelia: the lamellar olfactory epithelium (OE) and the recess epithelium (RecE). They are considered to correspond to the OE of teleost and a primitive vomeronasal organ (VNO), respectively. Cells expressing V1Rs were localized mainly in the lamellar OE and rarely in the RecE. In teleost, in which the VNO is absent, all olfactory receptors are expressed in the OE, while in Xenopus V1Rs are expressed exclusively in the OE, and not in the VNO. Our results imply that V1R expression in lungfish represents an intermediate step toward the complete segregation of V1R expression between the OE and the VNO, reflecting the phylogenetic position of lungfish between teleosts and amphibians.